1997
DOI: 10.1097/00005373-199706000-00017
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound Based Key Clinical Pathway Reduces the use of Hospital Resources for the Evaluation of Blunt Abdominal Trauma

Abstract: An ultrasound based KCP resulted in significant reductions in the use of invasive DPL and costly CT scanning in the evaluation of blunt abdominal trauma without risk to the patient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
65
0
4

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 137 publications
(70 citation statements)
references
References 16 publications
1
65
0
4
Order By: Relevance
“…In addition, smaller hospitals may not have CT as readily available; consequently, ultrasound would be important. Branney et al [26] developed a key clinical decision pathway using ultrasound in blunt trauma patients that reduced CT and DPL use and cost, without an increase in missed injuries. In addition, recent evidence in a randomized trial demonstrated that when ultrasound is absent, more abdominal CT scans were ordered, suggesting that some abdominal CT scans are being performed as ''screening'' tests, especially in patients with a low clinical probability of intra-abdominal injury [27].…”
Section: Clinical Implications Of the Focused Assessment With Sonogramentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, smaller hospitals may not have CT as readily available; consequently, ultrasound would be important. Branney et al [26] developed a key clinical decision pathway using ultrasound in blunt trauma patients that reduced CT and DPL use and cost, without an increase in missed injuries. In addition, recent evidence in a randomized trial demonstrated that when ultrasound is absent, more abdominal CT scans were ordered, suggesting that some abdominal CT scans are being performed as ''screening'' tests, especially in patients with a low clinical probability of intra-abdominal injury [27].…”
Section: Clinical Implications Of the Focused Assessment With Sonogramentioning
confidence: 99%
“…Another algorithm that is more logical and incorporates clinical and ultrasound data is the Key Clinical Pathway developed by Branney et al [26]. This pathway uses hemodynamic status first.…”
Section: Clinical Algorithmsmentioning
confidence: 99%
“…A study by Eanniello had only 16% of patients with positive CT findings who required a laparotomy. 16 Branney 17 found a 58% reduction in the use of CT using a protocol where haemodynamically unstable patients or those with signs of peritonitis with positive US findings underwent laparotomy, but those with negative US and normal physical examination were admitted for observation. The rate of missed injuries was not reported higher in those who did not have a CT. 3 It also had no impact on the duration of hospitalisation.…”
Section: Discussionmentioning
confidence: 99%
“…In order to detect pericardial, pleural with exam windows are used through which interior structures are imaged (2)(3)(4)(5)(6). In the setting of trauma, free intraabdominal or intrathoracic fluid indicates hemorhage (1,7,8). When compared to physical exam and CT imaging, bedside ultrasound is performed rapidly and assess accurate result in determining which patients needed emergency interventions (7,9,10).…”
Section: Introductionmentioning
confidence: 99%
“…In the setting of trauma, free intraabdominal or intrathoracic fluid indicates hemorhage (1,7,8). When compared to physical exam and CT imaging, bedside ultrasound is performed rapidly and assess accurate result in determining which patients needed emergency interventions (7,9,10). The aim of this study was to determine the usefulness of the FAST examination in first evaluation and observation of blunt trauma patients.…”
Section: Introductionmentioning
confidence: 99%